2018
DOI: 10.1139/cjfas-2017-0408
|View full text |Cite
|
Sign up to set email alerts
|

Egg size and lipid content of lake trout (Salvelinus namaycush) in the wild and in captivity

Abstract: Egg quality influences early life survival in fishes, but drivers of egg quality variation remain poorly understood. I examined egg quality of a long-lived, iteroparous salmonid (lake trout (Salvelinus namaycush)) with respect to maternal traits and environmental conditions in wild and captively reared populations. Variation was stronger and more consistent for egg size than for lipid content. Among females, egg size was most strongly related to maternal age, in both wild and captive populations, and faster-gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 89 publications
0
7
0
Order By: Relevance
“…In captive breeding, relaxed selection on embryos could give females with many small eggs an evolutionary advantage over females with few large eggs. This could lead to an evolutionary response and thereby decrease in mean egg size over time (Heath et al, 2003; Johnston, 2018). Our results suggest that such an evolutionary response would lead to smaller juveniles over time.…”
Section: Discussionmentioning
confidence: 99%
“…In captive breeding, relaxed selection on embryos could give females with many small eggs an evolutionary advantage over females with few large eggs. This could lead to an evolutionary response and thereby decrease in mean egg size over time (Heath et al, 2003; Johnston, 2018). Our results suggest that such an evolutionary response would lead to smaller juveniles over time.…”
Section: Discussionmentioning
confidence: 99%
“…The first is that the observed differences between juveniles from the two populations reared in the common garden study may be the result of differing parental effects, in which the parents' phenotypes influence those of offspring beyond the direct effects of genes (Räsänen and Kruuk 2007). This may take the form of gamete provisioning, in which the size, lipid content and/ or fatty acid composition of ova can play a role in eventual alevin phenotype and fitness (Wiegand et al 2007;Johnston 2018;Shaw et al 2018). Alternatively, transgenerational epigenetic effects may be responsible for the divergent phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…For example, several studies have associated rapid growth with more numerous, but smaller, eggs for fish of a given length (Bagenal, 1969; Morita et al, 1999). Conversely, Johnston (2018) found that faster‐growing female lake trout ( Salvelinus namaycush ) tended to produce larger eggs. Density‐dependent growth links the size of individuals to population density, and because smaller fish produce fewer eggs, the effect can propagate back to the population level (Watson et al, 2022).…”
Section: Introductionmentioning
confidence: 99%